Pengaruh Dosis Biokoagulan Ekstrak Belimbing Wuluh (Averrhoa Bilimbi) Dan Kecepatan Pengadukan Terhadap Penyisihan Zat Organik Dan Warna Pada Air Gambut - Febriana, Hertina; Daud, Syarfi; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Peat water qualitatively still has constraints such as organic matter and high color, but the use of quantitative peat water has the potential to be processed into clean water. The aim of this study was to study the effect of variations in the dosage of starfruit extract and the speed of stirring on the removal of organic substances and the color of peat water by coagulation and flocculation using the starfruit extract of biokoagulant. This research was carried out with variations in the dosage of starfruit extract of 45 mL, 50 mL, 55 mL, 60 mLÂ and the stirring speed variations of 100 rpm, 125 rpm, 150 rpm respectively. The results showed the highest removal efficiency of organic matter and color occurred at a dose of coagulant 60 mL / L with a stirring speed of 150 rpm each of 82.23% and 47.22%.Â Â Keywords: Peat Water, Dosage, Stirring Speed, Coagulation-Flocculation, Natural Coagulant